Identifying Adult Patients With Eating Disorder Symptoms in Outpatient Mental Health via a Two‐Item Screener - Lisa Ranzenhofer; Sara Lowmaster; Evelyn Attia (International Journal of Eating Disorders, 2026)
ABSTRACT Objective Patients with eating disorders (EDs) are often ill for many years before receiving treatment, a problem that may be addressed in part via improved screening. Given high rates of comorbidity with nearly all other psychiatric conditions, screening all patients in outpatient mental health settings provides an opportunity for detection and intervention. A very brief (i.e., 1–2 item) screener may be useful for determining who would benefit from additional query. Method A chart review was conducted to explore the utility of two ED screening items that were administered alongside SCOFF items as part of routine clinical care. Results Over a quarter (26.3%) of patients reported either eating or body image problems at a level of at least “Moderate/more than half” of days; 42.9% reported these problems at a level of at least “Mild/Some of the days”; 14.2% had a SCOFF score ≥ 2. Equal proportions of men and women were captured by both screeners. Utilizing “Mild/Some of the days” as a cutoff, over 90% of individuals with a SCOFF score ≥ 2 were captured by the 2‐item screener. Discussion Outpatients receiving mental health treatment report high rates of concerns with eating and body shape/weight. It may be possible to identify individuals in need of additional assessment via a very brief screener querying eating concerns and preoccupation with body shape/weight. Additional testing across settings, with more diverse individuals, comparison with a validated ED diagnostic assessment, and addressing other aspects of the screening process (i.e., next steps for positive screens), are critical for developing an effective screening procedure for outpatient mental health.